CMPH eBulletin - Issue no 5 (July 2018) eISSN 2636-9729 - Helmy, Hazmi (Universiti Malaysia Sarawak, (UNIMAS), 2018)
This is an eBulletin produced by the Department of Community Medicine and Public Health of the Faculty of Medicine and Health Sciences. It contains articles, researches write up, opinion pieces related to public health from members and students of the department.